Knowledge of primary school teachers regarding HIV/AIDS in Bichi local government Kano State, Nigeria - Mustapha, Abdu; Ismail, Suriani; Md Said, Salmiah; Ibrahim, Faisal; Syed Hassan, Syed Tajuddin; Yakasai, Musa Garba (Globeedu Group, 2017)
Introduction: The aim of this study was to assess the knowledge of primary school teachers as regard accurate understanding of the modes of HIV/AIDS transmission and its prevention strategies. This is necessary because, teachers are expected to play a major role in the provision of information leading to awareness and behavior change among the learners. Methods: A cross-sectional survey was conducted using simple random sampling design among primary school teachers in Bichi local government, Kano State, Nigeria. The study was conducted among 600 participants, and informed consent was provided with validated structured self-administered questionnaire. Data analysis was done using IBM SPSS version 22.0. Results: The level of HIV/AIDS knowledge among primary school teachers in Bichi local government, Kano State, Nigeria was low; 24.7% for good knowledge and 75.3% for poor knowledge. The teachers answered correctly about difference between HIV and AIDS at 59%, HIV/AIDS can be transmitted from mother to her baby at 41.2%, transmission through saliva, sweat and tears at 50%, sharing sharp objects at 66.8%. Also, only 34% accept antiretroviral therapy (ART) for preventive strategies, 34.8% said ‘Yes’ to statement that HIV can be prevented by not sharing sharp objects and about 50% accept condom as a preventive device. Conclusion: These findings highlight the need for HIV/AIDS education intervention for increasing HIV/AIDS-related knowledge of primary school teachers in Bichi local government, Kano State, Nigeria.